The Validity of Concept Attainment With Multi Representation as an Alternative Learning Model to Improve Students' Mastery of Concepts and Scientific Consistency - Pramonoadi; Sri Tresnaningsih; Abdul Faqih; Rahyu Setiani; Dwikoranto (Indonesia Approach Education, 2020)
The concept attainment tutorial tool with multi representations still needs to be developed. The purpose of this study is to describe the validity of the model and the validity of concept attainment devices with multi representations as alternative learning models to improve students' mastery of concepts and scientific consistency. The development of this tutorial tool uses the design of Plomp which consists of preliminary study phase, prototype stage, and assessment phase. The limited test was conducted on students of the Surabaya Open University in the Basic Science Natural Sciences course (PDGK4103). Research data were collected by the validation method using the model validation sheet instrument and the device validation sheet. Data were analyzed using qualitative descriptive analysis. The results of the study show that: (1) The concept of attainment model with multi representations developed is included in the valid criteria in terms of content validity and construct validity. (2) The multi-representation tutorial tool developed is included in the valid criteria. Based on the above it can be concluded that the concept of attainment with multi representations developed is valid and appropriate to be used to improve students' mastery of concepts and scientific consistency.